Body Conciousness Questionnaire (BCQ) Versi Bahasa Indonesia: Pengujian Properti Psikometri Menggunakan CFA dan Rasch Model - Bintang, Rahmat S.; Fischer, Isabell Nicole (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2025)
This study aims to test the psychometric properties of the Body Consciousness Questionnaire (BCQ) instrument which has been adapted into Indonesian. Data analysis in this study used a CFA approach to test the factor structure and Rasch model analysis to obtain better parameter estimates. The sample in this study was 304 respondents (male = 108; female = 196) with an age range of 18 - 24 years (mean age = 20.58; SD age = 1.52.). The sampling method used was non-probability sampling with purposive sampling technique. The results showed that the Body Consciousness Questionnaire (BCQ) instrument has a fit model to the data (unidimensional). In addition, this finding is supported by Rasch model analysis where the assumption of unidimensionality is met. Other findings related to local independence, item fit, reliability showed good results. The items in the adapted BCQ have been declared valid and appropriate to measure the construct of Body Consciousness.